V241F KCNQ1 Mutation Shortens Electrical Wavelength and Reduces Ventricular Pumping Capabilities: A Simulation Study With an Electro-Mechanical Model - Heikhmakhtiar, Aulia Khamas; Rasyidin, Fakhmi Adi; Lim, Ki Moo (Frontiers in Physics, 2018)
Death due to ventricular fibrillation (VF) can occur over a relatively short time period. During the first stage, an irregular heartbeat or arrhythmia of the heart may occur. Therefore, studying arrhythmia could reveal important insights relevant to the prevention of VF. One of the factors known to cause arrhythmia is the generation of mutations in the ion channels of myocytes. The current experimental methods to monitor and observe subjects with arrhythmia are invasive, and could possibly harm the subject with no guarantee of obtaining good results. These limitations could be overcome by using an extensively validated computational simulation study. This study aims to enhance our understanding of the effect of the V241F mutation on electromechanical behavior in the heart. We simulated three conditions; wild-type (WT), heterozygous/intermediate V241F, and pure V241F conditions in an electrophysiological single cell model and three-dimensional electro-mechanics ventricular model. The electro-mechanics model is a one-way coupling of the electrical compartment to the mechanical compartment by Ca2+ transient concentration. Consistent with a previous study, the V241F mutation significantly shortened the action potential duration at 90% repolarization (APD90) under pure V241F mutation conditions, due to the gain of function of the slow delayed rectifier potassium (IKs) channel. This APD90 shortening is associated with a short electrical wavelength, which shortens the Ca2+ activation time as well. The hemodynamic responses showed that the V241F mutation lowered ventricular contraction under normal sinus rhythm conditions by decreasing the stroke volume, stroke work, and ejection fraction. During reentry, the V241F mutation significantly reduced the ventricular contractility compared with the WT condition. In conclusions, the effect of the two variants of V241F (intermediate and pure) mutation not only disturbed the electrophysiological events but also affected the mechanical behavior significantly. The result of this study can be used as a reference for the cardiovascular expert to decide the appropriate pharmacology of IKs conductance block for the patient.